Photonic slot routing a cost effective approach to designingall-optical access and metro networks. - Elek, V.
In the backbone network, the high level of traffic aggregation achieved by numerous users is efficiently served by means of optical circuit switched solutions-the so-called wavelength routing approach. In the access and metro networks, on the contrary, the reduced level of traffic aggregation makes wavelength routing solutions inadequate. The finer and more dynamic bandwidth allocation provided by packet-interleaved optical time-division multiplexing is thus advocated in these network areas. This article presents a survey of an OTDM approach, known as photonic slot routing, or PSR. It is illustrated how this approach may provide a cost-effective solution to deploying all-optical access and metro networks with today's technology
Keywords: PSR; All-optical access networks; All-optical metro networks; Backbone network; Bandwidth allocation; Cost effective approach; Packet-interleaved optical time-division multiplexing; Photonic slot routing; Traffic aggregation